Collingwood's metaphysics a unique position - Vanheeswijck, Guido 1955- (Routledge, 2025)
"This book explores R.G. Collingwood's concept of metaphysics. It traces the evolution of Collingwood's thought on metaphysics through his published work, posthumously published manuscripts, and recently discovered course notes. From 1933 to 1936, Collingwood's thought shifted considerably from the more orthodox Hegelian treatment of metaphysics as the study of the general nature of reality, to the more 'historicist' study of absolute presuppositions. This radical-conversion-hypothesis has been for a long time the single most important issue in the interpretation of Collingwood's philosophy. This book provides a fresh reappraisal of his thinking on metaphysics during these crucial years. It argues that objective idealism is the key to unraveling the true scope of Collingwood's metaphysics. This theory takes a mid-position between mainstream interpretations in the secondary literature and forms the background to many of Collingwood's key ideas regarding metaphysics, the philosophy of nature and the philosophy of history. The book also compares Collingwood's concept of metaphysics to that of his predecessors, contemporaries, and followers. The second part of the book focuses in detail on the similarities and differences between Collingwood's metaphysics and, in chronological order, the views on metaphysics of Dilthey, Whitehead, Ayer, Wittgenstein, Heidegger, Berlin, Kolakowski, Strawson, and Taylor. Collingwood's Metaphysics will be of interest to scholars and graduate students interested in Collingwood's philosophy, 20th-century philosophy, and metaphysics"--
Keywords: Collingwood, Robin G. -- 1889-1943; Metaphysik; Collingwood, R. G. / (Robin George) / 1889-1943; Metaphysics; Métaphysique; metaphysics